Entropy and the Lymphatic System, a New Model with Therapeutic Potential (Global Journal of Medical Research, 2025)
A descriptor of life is a phase transition between order and chaos Entropy is the physical property of this transition determining lifespan Rules of maintaining entropy and a model of health and disease are presented simplifying scientific methods Entropy is a term that is poorly understood by physicists and unfamiliar to biologists Entropy in a biological context can be seen as a measure of systemic disorder with health representing a state of maintained low entropy The mechanism of maintaining order is the subject of this paper with emphasis on the organ of negative entropy the lymphatic system
Keywords: entropy; lymphatic system; glymphatic function; inflammation; progenitor cells; hs-crp; health model; biological order; regeneration; systems biology